Influence of Local Tumor Factors and Radiotherapy Dose on Prognosis of Clinical Stage T1-4N0M0 Esophageal Squamous Cell Carcinoma - Yan KONG; Qian DONG; Shuguang LI; Jinrui XU; Xiaohan ZHAO; Wenzhao DENG; Wenbin SHEN (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the effect of different radiotherapy doses on the prognosis of patients with stage cT1-4N0M0 esophageal squamous cell carcinoma (ESCC) who received radical radio (chemo)therapy categorized into subgroups with different tumor local factors. MethodsA retrospective analysis was conducted on 256 patients with clinically nonmetastatic esophageal squamous cell carcinoma. The optimal cutoff for tumor local factors was determined. The relationship between latest treatment efficacy and tumor local factors was analyzed, and independent indicators affecting patient overall survival (OS) were examined using multivariate analysis. The subgroup analysis was performed to determine the correlation between selected factors and radiation therapy doses. ResultsThe shorter the X-ray length of esophageal tumor lesion and the smaller the lesion canal wall thickness and gross tumor volume (GTV), the better the latest treatment efficacy of the patients (χ2=9.066, 10.310, 15.661, respectively, P=0.011, 0.006, P<0.001). Multivariate analysis results showed that GTV(P<0.001), radiation dose(P=0.038), and latest treatment efficacy(P<0.001) were independent predictors of the patients’ OS, and the latter two were also independent predictors of the patients’ progression-free survival (PFS) (P=0.033, <0.001). Subgroup analysis further showed that high doses of radiotherapy (over 60 Gy) resulted in good OS (χ2=5.040, 4.588, 5.400, P=0.025, 0.032, 0.020) and PFS (χ2=6.089, 4.353, 6.459, P=0.014, 0.037, 0.011) in the subgroup with maximum wall thickness below 3.7 cm, with esophageal lesions with GTV below 37.34 cm3, or not receiving simultaneous chemotherapy. ConclusionLocal tumor factors are important prognostic factors of ESCC patients treated with radical radio(chemo)therapy. Patients with thin lesion walls and small tumor volumes may greatly benefit from high doses of radiation (over 60 Gy).